1970
DOI: 10.3126/njenthns.v1i2.4755
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Sinonasal Tumors in Eastern Nepal

Abstract: Keywords: Carcinoma; maxillectomy, papilloma; sinonasal tumorDOI: 10.3126/njenthns.v1i2.4755 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.9-11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The predominance of female seen in this study is in contrast with the previous study conducted in our center that reported equal gender affectation 8 and other reports; 3 9 10 however, it is in agreement with a recent study conducted by Fasunla and Ogunkeyede 11 in Ibadan. In our environment, cooking is still being considered as women's job, and more than 55% of the patients in this study were exposed to wood dust most likely in the form of firewood for cooking, and unconfirmed report also showed that women present early to the hospital than male counterpart.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The predominance of female seen in this study is in contrast with the previous study conducted in our center that reported equal gender affectation 8 and other reports; 3 9 10 however, it is in agreement with a recent study conducted by Fasunla and Ogunkeyede 11 in Ibadan. In our environment, cooking is still being considered as women's job, and more than 55% of the patients in this study were exposed to wood dust most likely in the form of firewood for cooking, and unconfirmed report also showed that women present early to the hospital than male counterpart.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the involvement of females in similar occupation with their male counterparts for socioeconomic gain which exposed them to the risk factors of sinonasal tumors such as woodwork, leatherwork, and exposure to petrochemicals might also be a contributory factor to the increased female affectation. 9 10…”
Section: Discussionmentioning
confidence: 99%
“…However; other studies have noted predominance of benign tumors over the malignant ones. [9][10][11] Since our study was based at cancer hospital where diagnosed malignant cases are referred for further management; it may have led to predominance of malignant ones.…”
Section: Discussionmentioning
confidence: 99%
“…9 No data on incidence of melanoma in Nepal were available except for only a few reported cases of melanoma in vagina, eyes and nasal cavity. 7,10,11 In the study conducted by Nagore E et al in Spain, the total number of cases enrolled in the study was 1571 over a period of 18 years. 8 But in the study conducted by Hui S K et al in Hong Kong Chinese patients over a period of 12 years, the total number of cases was only 32.…”
Section: Discussionmentioning
confidence: 99%